Cross-Border Shopping: Evidence and Welfare Implications for Switzerland - Ariel Burstein; Sarah Lein; Jonathan Vogel (CESifo GmbH, 2024)
Consumers access foreign goods by purchasing them domestically or shopping abroad. We present new facts on cross-border shopping by Swiss households showing, for example, that prices of identical products are lower in neighboring countries, cross-border shopping shares fall with distance to the border, and price gaps and cross-border shopping shares rose following the 2015 Swiss Franc appreciation. We use a simple model of cross-border shopping to quantify how variation across space in cross-border shopping results in heterogeneous changes in cost-of-living in response to changes in international prices such as the 2015 Swiss Franc Appreciation and the 2020 Covid-19-related closing of the border.
Keywords: E31; F10; F41; F60; 330; cross-border shopping; cost of living; household heterogeneity